King and Queen of the High Cs : the Bel Canto Love Affair of Luciano Pavarotti and Joan Sutherland - Hacker, Jonas; Kenneavy, Erin (My University, 2011)
Luciano Pavarotti and Joan Sutherland were masters of the opera style known as bel canto, or "beautiful singing." This study chose six bel canto operas that the duo recorded and selected scenes that are accessible for undergraduate singers, specifically sopranos and tenors. Through transcriptions of ornamentation, interviews, listening analyses, and an extensive literature review, we created "listening guides" that students and teachers could use in their own study.
Color poster with text and images.
Keywords: Operas--Analysis, appreciation; Pavarotti, Luciano; Sutherland, Joan, 1926-; Opera--Performance; Bel canto; Posters